Low literacy: a hidden problem in family planning clinics. Issue 4 (1st October 2006) - Rutherford, Jeanne; Taylor, Avril; Holman, Ruth; MacDonald, John; Jarrett, Dominic; Bigrigg, Alison
Abstract : Objectives: Low literacy is highly prevalent among UK adults. This study assessed functional health literacy among family planning clinic clients and whether this was associated with sexual health knowledge and behaviours. It also assessed the readability of patient leaflets. Methods: 505 female family planning clinic attendees aged 16–35 years were interviewed about their sexual behaviour and knowledge. Their reading age was assessed using a validated test (REALM). The readability of leaflets on contraception supplied to clinic users was measured. Results: All respondents had a reading age of 12 years and above, 221 (43.8%) between 12 and 14 years and 284 (56.2%) greater than 14 years. Those in the lower literacy group were significantly more likely to have been aged under 16 years at time of first sexual intercourse, and significantly less likely to know the most fertile time of the menstrual cycle, to identify sexually transmitted infections and to know that sexual infections can be transmitted through oral and anal sex. The reading age of information leaflets in the clinics ranged from 11 to 17 years. Thus, clients with a reading level of 12–14 years would have difficulty in understanding some of the leaflets. Conclusions: Functional health literacy is related to sexual behaviour and knowledge. Written information should be prepared with this in mind and other routes of communication considered.